Acquiring credentials in bedside ultrasound: a cross-sectional survey - Lewiss, Resa E (BMJ Publishing Group, 2013)
OBJECTIVE: Although there are training guidelines to credential emergency physicians in bedside ultrasound, many faculty groups have members who completed residency without a mandatory curriculum. These physicians are therefore required to learn bedside ultrasound while out in practice. The objective of this descriptive report is to illustrate a single academic facility's experience with acquiring credentials for emergency physicians in bedside ultrasound and the faculty's impressions on the motivators of and barriers to completion of the requirements. DESIGN: Cross-sectional survey. SETTING: Two urban teaching hospitals with a combined volume of 170 000 visits a year. PARTICIPANTS: 41 emergency medicine attending physicians. INTERVENTION: Emergency medicine attending physicians underwent training and credentialing in the applications of aorta and pelvic ultrasound over a 9-month period. OUTCOME MEASURE: After the credentialing period, we conducted a survey to evaluate the physicians’ perceptions of this process. RESULTS: There were 41 faculty members during the credentialing survey period. 11 of the faculty members were exempt from ultrasound training. We asked attending physicians (N=41 exempt and non-exempt) to complete a web-based survey after the completion of the credentialing period. Questions about the potential barriers and incentives were listed and responders were asked to rank answers on a five-point Likert scale. Of the 31 respondents, 21 (67.7%) completed the credentialing requirements by the 9-month deadline. 19 of 26 emergency medicine residency trained physicians completed the requirements compared with 2/5 of those that were not emergency medicine residency trained. Our pilot study data suggest an association between fewer years in practice and completion of the requirements. CONCLUSIONS: This is a report on a single academic institution's experience with a faculty credentialing programme in bedside ultrasound for physicians with a diversity of prior experience in bedside ultrasonography. We describe the success of the credentialing process and identify survey-based faculty characteristics associated with fulfilling the requirements.